The K3 type killer strains of genus Saccharomyces for wine production - Sulo, P; Michalcáková, S (Folia microbiologica, 1992)
Using simultaneous fusion of protoplasts of three strains the auxotrophic K3 killer designated MH1 was prepared at a very low frequency and further employed for the transfer of the K3 killer character into a commercial wine yeast. A novel Saccharomyces Bratislava 1K3 strain with desirable technological and anti-yeast killer abilities was thus constructed. Attempts to prepare double K1/K3 killers were made. The obtained fusion products contained M1 dsRNA and were able to produce only the K1 type killer toxin.
Keywords: Wine; Industrial Microbiology; RNA, Fungal; Protoplasts; Saccharomyces; průmyslová mikrobiologie; protoplasty; víno; fungální RNA